Komunikasi oro-antral paska pencabutan sisa akar gigi 16 - Dipankara, Jackson; Lulu Afifah Himawan, Dinda; Poedjiastoeti, Wiwiek (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
The opening of the sinus cavity due to tooth extraction, infection, or some complications so that an abnormal pathway is formed is oroantral communication. If the abnormal pathway fails to close, it turns into an oro-antral fistula. In this case report, patients performed tooth 16 and 17 extractions, but oroantral communication only occurred in the socket after tooth extraction 16. The diagnosis of oroantral communication is established based on the patient's complaints when gargling after tooth extraction, patients complain of water coming out of the nasal cavity and smell of blood. Then it was confirmed by clinical examination by instructing the patient to close the nose and then blow air while examining the retraction socket area, the results of the examination showed air passing through the blood in the retraction socket. The management of this case is done by giving a gelatin sponge into the socket and suturing with the figure of eight techniques or with non-surgical treatment. The results of the treatment showed the closure of oroantral communication.